2021
DOI: 10.2991/ahsr.k.210115.117
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effect of Moringa oleifera Aqueous Extract in Diabetic Animal Studies: A Mechanisms Review

Abstract: Diabetes is a chronic hyperglycemic condition which the therapy by maintaining blood glucose levels. Herbal plants can be an alternative therapy in reducing blood glucose levels. Indonesia is rich in herbaceous plants, one of which is Moringa oleifera Lam. Herbal plant of Moringa oleifera Lam. has been ethnopharmacology to reduce blood glucose levels. This review purpose of explaining the existing literature published until June 2020 on the mechanism of aqueous extract of Moringa oleifera leaves in hypoglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This might indicate that Moringa has an insulin-like impact on peripheral tissues, either by boosting glucose uptake and metabolism or by inhibiting gluconeogenesis. It is likely that the aqueous extract of the moringa leaves has some effect of increasing the tissue utilization of glucose (Gray et al, 2000, Oyedepo et al, 2013 by inhibiting hepatic gluconeogenesis or absorption of glucose into the muscles and adipose tissues (Pradana, et al, 2021). However, Ahemen et al (2013) reported insignificant influence of diet containing MOL on glucose in rabbit serum.…”
Section: Results and Discussion I-the Effect Of Moringa Olifera Leavesmentioning
confidence: 99%
“…This might indicate that Moringa has an insulin-like impact on peripheral tissues, either by boosting glucose uptake and metabolism or by inhibiting gluconeogenesis. It is likely that the aqueous extract of the moringa leaves has some effect of increasing the tissue utilization of glucose (Gray et al, 2000, Oyedepo et al, 2013 by inhibiting hepatic gluconeogenesis or absorption of glucose into the muscles and adipose tissues (Pradana, et al, 2021). However, Ahemen et al (2013) reported insignificant influence of diet containing MOL on glucose in rabbit serum.…”
Section: Results and Discussion I-the Effect Of Moringa Olifera Leavesmentioning
confidence: 99%
“…Moringa oleifera (Moringa) is native to India and is used in many areas of human life due to the macro and microelements it contains [1][2][3]. It is known that Moringa has a hypoglycemic influence [4] and the water extract of its leaves may be used for Diabetes mellitus to reduce the blood glucose level [5]. It was shown that the extract of the Moringa leaves inhibits intestinal α-glucosidase, pancreatic cholesterol esterase, and pancreatic lipase activities, thus helping in the treatment of diabetes mellitus [6].…”
Section: Introductionmentioning
confidence: 99%